Hubungan Berfikir Terbuka Secara Aktif dengan Kebencian pada Pemilih Figur Calon Presiden - Fida Amina Zahro; Yuni Nurhamida; Alifah Nabilah Masturah (Universitas Muhammadiyah Jember, 2021)
2019 is the following year after 5 years ago carrying out presidential elections for Indonesia. Indonesia has a routine every 5 years carrying out the General Election (General Election) to accommodate the people's aspirations for their country and choose the best head of state according to the community. With this, there must be candidates who will advance in the election and there will also be differences in the political game in it. The existence of this creates a conflict that will affect the traces of opinion among the people and cause hatred. One of the factors that influence hatred is politics. A science to achieve power as desired and gain profits. The aim of the study was to find out the relationship between active open thinking and hatred towards the supporters of selected presidential candidates. The sampling technique uses accidental sampling in Malang. The research subjects were 300 people ranging in age from 17-25 years. There are several criteria sampled in this study, namely having a KTP, already having the right to vote for the 2019 presidential election. The data collection method uses a scale and analysis test using a correlation test showing the existence of a negative relationship between active open thinking and hatred of supporters of presidential candidates.